Preparation and properties of degradable durian seed starch/low density polyethlene and durian seed starch/poli (e-caprolactone)composites - Nur Farahana Ramli (School of Materials Engineering, Universiti Malaysia Perlis, 2012)
i- To investigate the effect of DSS on the properties of the DSS/LDPE and DSS/PCL composites. ii- To investigate the effcet of DSS on the properties of DSS filled PCL/LDPE hybrid composites. iii- To investigate the biodegradability of the DSS/LDPE, DSS/PCL and PCL/LDPE/DSS composites.